Size Segregation of Gold Nanoparticles into Bilayer-like Vesicular Assembly - Wei, Jinjian (Langmuir : the ACS journal of surfaces and colloids, 2023)
Size segregation of nanoparticles with different sizes into highly ordered, unique nanostructures is important for their practical applications. Herein, we demonstrate spontaneous self-assembly of the binary mixtures of small and large gold nanoparticles (GNPs; 5/15, 5/20, or 10/20 in diameter) in the presence of a tetra(ethylene glycol)-terminated octafluoro-4,4'-biphenol ligand, namely, TeOFBL, resulting in a size-segregated assembly. The outer single layer of large GNPs forming a gold nanoparticle vesicle (GNV) encapsulated the inner vesicle-like assembly composed of small GNPs, which is referred to as bilayer-like GNV and similar to the molecular bilayer structure of a liposome. The size segregation was driven by the solvophobic feature of the TeOFBLs on the surface of GNPs. A time-course study indicated that size segregation occurred instantaneously during the mixing stage of the self-organization process. The size-segregated precursors quickly fused with each other through the inner-inner and outer-outer layer fashion to form the bilayer-like GNV. This study provides a new approach to creating biomimetic bilayer capsules with different physical properties for potential applications such as surface-enhanced Raman scattering and drug delivery